Faktor-faktor yang Mempengaruhi Keputusan Muzakki Membayar Zakat dengan Kepercayaan sebagai Variabel Intervening di Lazismu Kota Palembang - Angle Dwi Carolina; ⁠Peny Cahaya Azwari; ⁠Siti Mardiah (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2026)
This study aims to examine the effect of institutional image and digital payment on zakat payers’ decisions to pay zakat, with trust as an intervening variable at LAZISMU Palembang City. This study employs a quantitative research design using primary data collected through questionnaires distributed to zakat payers in Palembang City. Data were analyzed using the Theory of Planned Behavior (TPB), where institutional image represents attitude toward behavior, digital payment reflects perceived behavioral control, and trust functions as an intervening variable influencing zakat payment decisions. The results show that a positive institutional image characterized by professionalism, transparency, and integrity significantly enhances zakat payers’ trust, which in turn strengthens their decision to pay zakat through LAZISMU. Furthermore, digital payment systems that are perceived as easy, secure, and beneficial positively influence zakat payment decisions, particularly when supported by a high level of trust. This study contributes theoretically to the development of zakat management literature and provides empirical insights for strengthening institutional credibility and digital-based zakat services.